569 Trial Without Catheter – Are We Performing the Procedure Correctly?. (19th August 2022) - Mehta, A; Arang, H; Anyomih, T; Arsanious, N
Abstract: Aim: To assess the trial without catheter (TWOC) practice at our unit by ensuring there is accurate recording of data onto electronic records and factors affecting successful TWOC are being addressed. Method: 2 months of retrospective data on TWOC practice was collected between 01/07/2019–30/08/2019. The Guy's and St Thomas' TWOC guideline was used as the standard to compare to. Factors that could affect TWOC outcomes were checked on our electronic patient records. A re-audit was performed between 31/07/2020–30/08/2020. Results: 55 sets of data were collected with 16 (42%) patients having no documentation of post void residual volume (PVR). There were 6 adverse outcomes following TWOC, 3 patients returned in acute urinary retention (AUR) and 3 had delayed discharges. 3/6 of these adverse outcomes were linked to poor TWOC practice. 4/5 patients who failed TWOC were not on Tamsulosin and 0/5 were on laxatives. Following our implemented changes the re-audit showed no adverse outcomes, and only 2 patients without PVR documented. Conclusions: Our first audit demonstrated significant adverse outcomes from poor TWOC practices at our unit. We implemented changes including writing an official TWOC guideline for the trust and regional teaching from our catheter workshop that included correct TWOC practice. Following these changes, the rates of adverse outcomes following TWOC were significantly reduced.